Techno‐Economic Evaluation of The Production of Resin-Based Brake Pads using Agricultural Wastes: Comparison of Eggshells/Banana Peels Brake Pads and Commercial Asbestos Brake Pads - Ragadhita, Risti; Al Husaeni, Dwi Fitria; Nandiyanto, Asep Bayu Dani (ASEAN Journal of Science and Engineering, 2023)
The purpose of this study was to analyze, evaluate, and compare the results of the feasibility analysis of producing egg shells/banana peels brake pads and commercial asbestos brake pads based on engineering and economic perspectives. Mass balance and several economic parameters (i.e., gross profit margin (GPM), payback period (PBP), break-even point (BEP), cumulative net present value (CNPV), and profitability index (PI)) are calculated to analyze the feasibility projects based on engineering and economic perspectives, respectively. The process of analyzing the economic feasibility of the project is assumed to be in ideal conditions. The engineering perspective shows that the project of banana peels/egg shells brake pads and commercial asbestos brake pads are prospective if the fabrication uses simple apparatus on a large scale. Economic evaluations such as GPM, PBP, BEP, CNPV, and PI all returned positive results, indicating that the project has the potential for large-scale production. It is hoped that the research could well demonstrate the project's importance for future development and serve as a model for future production of brake pads made from agricultural waste.